A NANO-AgI electrode with a regular hexagonal nanostructure and its preparation method and application
By using NANO-AgI electrode with regular regular hexagonal nanostructures, the problem of insufficient CO selectivity during electrocatalytic reduction of carbon dioxide is solved, and the effect of efficient conversion of CO2 to CO is achieved, with high activity and stability.
Patent Information
- Application Number
- CN202210833029.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-07-14
AI Technical Summary
In the prior art, when electrocatalyzed reduction of carbon dioxide, CO is insufficient in selectivity, making it difficult to achieve efficient conversion into chemicals of industrial value.
The NANO-AgI electrode with a regular hexagonal nanostructure was prepared by coating the NANO-AgI solution on the electrode substrate and forming a film. The reaction temperature of the mixed solution of silver ions, polymer dispersants and iodine ions was adjusted to 60°C to 70°C to form a catalytic electrode with a unique nanoparticle structure.
The selectivity of CO2 electrocatalytic reduction in CO2 is achieved to produce CO, and the electrode has high CO activity and excellent stability, which can efficiently convert CO2 into CO.
Smart Images

Figure CN115369446B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a NANO-AgI electrode with a regular hexagonal nanostructure, a preparation method and application of the electrode in an electrocatalytic reduction reaction of carbon dioxide. Background Art
[0002] The accelerated industrialization process has led to an increasing demand for energy, resulting in an increase in CO2 emissions, which is expected to have potential negative impacts on climate change, sea level rise and ocean acidification. In recent years, the conversion of CO2 into valuable hydrocarbons or other organic chemical fuels by electrochemical methods can not only solve the problem of energy shortage, but also help maintain the atmospheric carbon balance and reduce the greenhouse effect, which has important research significance. If we can use mature and efficient technology and select suitable catalysts to convert CO2 in the atmosphere into energy fuels such as CO through electrocatalytic technology, we can solve various environmental problems while providing renewable clean energy for part of industrial production, which will play a key role in promoting our realization of energy conservation and emission reduction and alleviating the energy crisis.
[0003] Ag-based catalysts have become the most commonly used materials due to their advantages such as high product selectivity, suitable exposure surface, environmental harmlessness and high economic applicability. The main product of the electrocatalytic reduction of CO2 is CO. As the main component of syngas, CO is an indispensable material for the production of a series of basic organic chemicals and intermediates, and is widely used in the chemical and metallurgical industries. At present, the development of new high-performance Ag-based catalysts to improve the selectivity of CO is an effective strategy to promote the rapid development of electrocatalytic carbon dioxide. Summary of the invention
[0004] The object of the present invention is to provide a NANO-AgI electrode with a regular regular hexagonal nanostructure so that the selectivity of the gas product CO generated by the electrocatalytic reduction of CO2 is close to 100%. The object of the present invention is also to provide a preparation method and application of the NANO-AgI electrode with a regular regular hexagonal nanostructure.
[0005] In a first aspect, the present invention provides a NANO-AgI electrode having a regular hexagonal nanostructure, which is obtained by coating a NANO-AgI solution on an electrode substrate and forming a film. The NANO-AgI solution adds a salt solution containing silver ions to a mixed solution of a polymer dispersant and a salt containing iodine ions, and reacts under continuous stirring at a temperature of 60°C to 70°C until the solution is in a milky white colloid state.
[0006] Preferably, the Ag in the NANO-AgI electrode + The molar amount of loading is 0.025mmol / cm 2 .
[0007] Preferably, the reaction time after adding the silver ion-containing salt solution to the mixed solution of the polymer dispersant and the iodide ion-containing salt is greater than or equal to 30 minutes.
[0008] Preferably, the polymer dispersant is polyvinyl pyrrolidone. The silver ion salt is AgNO3; the iodide ion salt is KI. In the mixed solution of polyvinyl pyrrolidone and KI, the molar ratio of polyvinyl pyrrolidone to KI is (0.0005-0.004):(0.2-0.7).
[0009] Preferably, the solvents of the AgNO3 solution and the mixed solution of polyvinyl pyrrolidone and KI are ethylene glycol. + The molar concentration of AgNO3 solution is 1 / 70mol / L~7 / 80mol / L. + The molar concentration is 0.15mol / L~0.6mol / L.
[0010] Preferably, the electrode substrate is made of carbon paper.
[0011] Preferably, the NANO-AgI solution is formed into a film on the electrode substrate by baking with an infrared lamp.
[0012] Preferably, the stirring speed after adding the silver ion-containing salt solution to the mixed solution of the polymer dispersant and the iodide ion-containing salt is 700 rpm to 900 rpm.
[0013] In a second aspect, the present invention provides a method for preparing the aforementioned NANO-AgI electrode having a regular hexagonal nanostructure, which comprises the following steps:
[0014] Step 1: Preparation of dispersant and solvent:
[0015] The ethylene glycol solution of polyvinyl pyrrolidone and KI was heated to 60°C to 70°C while stirring at a rotation speed of 1000 to 1500 rpm.
[0016] Step 2: Introduction of silver source:
[0017] Add the ethylene glycol solution of AgNO3 into the ethylene glycol solution of polyvinyl pyrrolidone and KI and stir evenly.
[0018] Step 3: Formation of regular hexagonal nanostructured NANO-AgI solution:
[0019] The mixed solution obtained in step 2 is reacted at a stirring speed of 700 to 900 rpm and a reaction temperature of 60° C. to 70° C. until the solution becomes a milky white colloid, thereby obtaining a NANO-AgI solution.
[0020] Step 4: Preparation and coating of electrodes:
[0021] After adding a binder to the NANO-AgI solution obtained in step 3, the solution is coated on carbon paper to form a NANO-AgI electrode with a regular hexagonal nanostructure.
[0022] In a third aspect, the present invention provides an application of the aforementioned NANO-AgI electrode having a regular hexagonal nanostructure in the electrocatalytic reduction of carbon dioxide to generate carbon monoxide.
[0023] Preferably, the NANO-AgI electrode having a regular hexagonal nanostructure is used as a working electrode in the electrocatalytic reaction; the reaction voltage of the working electrode is -1.6V to -1.9V.
[0024] The beneficial effects achieved by the present invention are:
[0025] 1. The present invention adjusts the reaction temperature of the mixed solution of silver ions, polymer dispersants, and iodine ions to 60°C to 70°C, so that the formed NANO-AgI electrode has a unique regular hexagonal structure. The surface of the catalytic electrode contains abundant active sites and has a unique nanoparticle structure, which increases the contact area between the electrode and the reactant and promotes the high selectivity of product generation. The NANO-AgI electrode provided by the present invention can be used to electrocatalytically reduce CO2 to obtain fuels and chemicals with industrial value, laying a foundation for the sustainable development and utilization of resources.
[0026] 2. The present invention adopts a water bath heating method and uses AgNO3 as a silver source to synthesize a NANO-AgI electrode with a regular hexagonal nanostructure. The electrode of the present invention has a very high selectivity for CO2 electrocatalytic reduction to produce CO, reaching 98.1%, and the electrode also has a high CO production activity and excellent stability. CO, as the main component of synthesis gas and various types of coal gas, is widely used in the metallurgical industry and various chemical processing industries.
[0027] 3. The NANO-AgI electrode with a regular hexagonal nanostructure provided by the present invention is produced by a simple, easy-to-operate and green synthesis step, and is expected to become a key technology for changing catalyst performance in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the NANO-AgI electrode with a regular hexagonal nanostructure prepared in Example 1 of the present invention;
[0029] Figure 2 This is a scanning electron microscope image of the NANO-AgI electrode prepared in Comparative Example 1 of the present invention;
[0030] Figure 3 A schematic diagram of a reaction device used in a comparative experiment of electrodes obtained in Example 1 and Comparative Example 1;
[0031] Figure 4 Schematic diagram of a comparative experiment of the electrodes obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with specific examples, but the protection scope of the present invention is not limited thereto.
[0033] Example 1
[0034] A method for preparing a NANO-AgI electrode having a regular hexagonal nanostructure comprises the following steps:
[0035] Step 1: Preparation of dispersant and solvent:
[0036] The mixed solution of polyvinyl pyrrolidone, KI and ethylene glycol was heated to 65°C in a constant temperature water bath under vigorous magnetic stirring (rotation speed of 1000-1500 rpm); the amount of polyvinyl pyrrolidone in the mixed solution was 0.001 mmol; the amount of I in KI was 0.001 mmol; - The amount of substance is 0.4mmol; the volume of ethylene glycol is 8-14ml.
[0037] Step 2: Introduction of silver source:
[0038] When the temperature of the mixed solution obtained in step 1 is stabilized to 65° C., 0.3 mmol of AgNO3 crystals are added to ethylene glycol with a volume of about 0.5 to 2 ml, and AgNO3 is fully dissolved in the ethylene glycol solvent; then the ethylene glycol solution of AgNO3 is quickly added to the mixed solution of polyvinyl pyrrolidone, KI and ethylene glycol obtained in step 1, and the mixture is fully and evenly mixed, and strong stirring is continuously provided to obtain a mixed solution after the introduction of the silver source.
[0039] Step 3: Formation of regular hexagonal nanostructured NANO-AgI solution:
[0040] The mixed solution after the introduction of the silver source was heated continuously for 45 minutes at a stirring speed of 700 to 900 rpm and a reaction temperature of 65° C., until it was clearly observed that the solution changed from transparent to a milky white and viscous colloid, and then the heating and stirring were stopped to obtain a NANO-AgI solution.
[0041] Step 4: Preparation and coating of electrodes:
[0042] Take 1 ml of NANO-AgI solution and add 70 μl of Nafion binder solution to 1 ml of NANO-AgI solution and ultrasonicate for 45 minutes to prepare NANO-AgI catalyst ink. Then, take 400 μl of NANO-AgI catalyst ink and apply the ink evenly to the cut area of 1×1 cm with a pipette. 2 The front and back sides of carbon paper with a thickness of 0.2 mm were coated with an infrared lamp until the NANO-AgI catalyst ink formed a film on the surface of the carbon paper, thereby obtaining a NANO-AgI electrode.
[0043] The electron microscope scanning image of the obtained NANO-AgI electrode is shown in Figure 1 As shown, it can be observed that its crystal morphology is a regular hexagon.
[0044] Example 2
[0045] A method for preparing a NANO-AgI electrode having a regular regular hexagonal nanostructure, the difference between this embodiment and embodiment 1 is that the reaction temperature in step 3 is 70° C. The crystal morphology of the obtained NANO-AgI electrode is a regular regular hexagon.
[0046] Example 3
[0047] A method for preparing a NANO-AgI electrode having a regular regular hexagonal nanostructure, the difference between this embodiment and embodiment 1 is that the reaction temperature in step 3 is 60° C. The crystal morphology of the obtained NANO-AgI electrode is a regular regular hexagon.
[0048] Comparative Example 1
[0049] A method for preparing a NANO-AgI electrode. The difference between this comparative example and Example 1 is that the reaction temperature in step three is 25°C.
[0050] The electron microscope scanning image of the obtained NANO-AgI electrode is shown in Figure 2 As shown, it can be observed that its crystal morphology does not form a regular hexagon.
[0051] In order to prove that the NANO-AgI electrode with regular hexagonal nanostructure obtained in Example 1 has significant superiority in electrocatalyzing carbon dioxide to produce carbon monoxide compared with the NANO-AgI electrode prepared in Comparative Example 1, the following comparative experiment was conducted.
[0052] like Figure 3As shown, the reaction device used in the experiment includes an H-type reactor, an acrylic water tank 2, a magnetic stirrer 3, a gas sampling needle 4, a constant temperature water bath 5, an electrochemical workstation 6 and a carbon dioxide gas source 7. The H-type reactor includes a cathode tank a, an anode tank b, an exchange channel connecting the cathode tank a and the anode tank b, and a cation exchange membrane 1-3 arranged in the exchange channel. A working electrode 1-1 and a reference electrode 1-2 are arranged in the cathode tank a. A counter electrode 1-4 is arranged in the anode tank. The reference electrode 1-2 adopts an Ag / AgCl electrode. The counter electrode 1-4 adopts a platinum electrode.
[0053] The electrolyte in the cathode tank a is a 0.1 mol / L KHCO3 solution (volume 120 ml) that is saturated with CO2; the electrolyte in the anode tank is a 0.5 mol / L NaOH solution (volume 120 ml). The working electrode 1-1, the reference electrode 1-2 and the counter electrode 1-4 are all connected to the electrochemical workstation 6. A gas inlet is provided at the top of the cathode tank a; the gas inlet is connected to the gas outlet of the carbon dioxide gas source 7. The carbon dioxide gas source 7 uses a gas cylinder filled with compressed CO2. The cathode tank needs to be sealed to prevent gas leakage; the H-type reactor is set in the acrylic water tank 2. A magnetic stirrer 3 is set below the acrylic water tank 2.
[0054] The experimental conditions are: applying a working voltage of -1.7V to the working electrode 1-1, and performing the electrocatalytic reduction of carbon dioxide reaction for 2 hours. During the reaction, the gas portion in the upper part of the cathode tank is sampled and analyzed every 30 minutes, and the current density and charge of the product at each time point are recorded respectively, and an optimal value is taken for subsequent calculation and analysis.
[0055] An experimental group and a control group were set up; the working electrode 1-1 in the experimental group adopted the NANO-AgI electrode with a regular hexagonal nanostructure prepared in Example 1; the working electrode 1-1 in the control group adopted the NANO-AgI electrode with a nanostructure prepared in Comparative Example 1.
[0056] The experimental results are as follows Figure 4 As shown, when the NANO-AgI electrode with regular hexagonal nanostructure prepared in Example 1 is used as the working electrode, the Faraday efficiency of CO2 electrocatalytic reduction to CO is 97.39%, and the electrocatalytic performance is very good; while when the NANO-AgI electrode with the nanostructure prepared in Comparative Example 1 is used as the working electrode, the Faraday efficiency of CO2 electrocatalytic reduction to CO is only 55.59%, indicating that the reaction temperature in step 3 of the embodiment has a significant influence on the crystal morphology of the obtained NANO-AgI electrode, and the effect of electrocatalytic reduction of CO2 to generate CO.
[0057] In order to demonstrate the electrocatalytic reduction effect of the NANO-AgI electrode with regular hexagonal nanostructure obtained in Example 1 at different voltages on carbon dioxide, the following comparative experiment was conducted.
[0058] Eleven independent experimental groups were set up; the difference between the 11 experimental groups was the different working potentials; the working electrodes 1-1 of the 11 experimental groups all used the NANO-AgI electrode prepared in Example 1, and the working potentials were -1.8V, -0.9V, -1.0V, -1.1V, -1.2V, -1.3V, -1.4V, -1.5V, -1.6V, -1.7V, and -1.9V, respectively. The results of the 11 experimental groups are shown in Table 1.
[0059] Table 1. Comparison of the Faradaic efficiency and current density of the electrodes obtained in Example 1 for the electrocatalytic reduction of CO2 at different potentials to generate CO
[0060]
[0061]
[0062] As can be seen from Table 1, the NANO-AgI electrode with a regular hexagonal nanostructure prepared in Example 1 is applied to the electrocatalytic reduction of carbon dioxide. At the optimal potential of -1.8V, the selectivity of the product CO (represented by the Faraday efficiency) is as high as 98.1%, and CO2 can be efficiently converted into CO. This is because the regular hexagonal nanostructure synthesized by the present invention provides more active sites and increases the contact area with the CO2 molecule, thereby improving the selectivity for CO when reducing CO2.
[0063] In addition, the current density of the NANO-AgI electrode with regular hexagonal nanostructure during the electrocatalytic reduction of CO2 also increases with the increase of the applied potential (experimental group 1 to experimental group 11). At the optimal reaction potential of -1.8V, the current density of the NANO-AgI electrode with regular hexagonal nanostructure prepared in Example 1 for CO is as high as 11.9mAcm -2 , thus showing higher activity for CO generation.
[0064] It can be seen that the NANO-AgI electrode with a regular hexagonal nanostructure shows extremely high selectivity for the product CO during the electrocatalytic reduction of CO2, close to 100%, and its activity for CO production is also significantly higher. Therefore, the electrode achieves efficient conversion from CO2 electrocatalytic reduction to CO and provides new scientific and technological support elements for the resource utilization of CO2.
Claims
1. A NANO-AgI electrode having a regular hexagonal nanostructure, characterized in that: The NANO-AgI solution is prepared by adding Nafion adhesive to the NANO-AgI solution, coating the solution on carbon paper and forming a film; the NANO-AgI solution is prepared by adding a salt solution containing silver ions to a mixed solution of a polymer dispersant and a salt containing iodine ions, and reacting the solution at a temperature of 60°C to 70°C while continuously stirring until the solution becomes a milky white colloid; The polymer dispersant is polyvinyl pyrrolidone; the salt of silver ions is AgNO3; the salt containing iodine ions is KI; the solvents of the AgNO3 solution and the mixed solution of polyvinyl pyrrolidone and KI are both ethylene glycol.
2. The NANO-AgI electrode having a regular hexagonal nanostructure according to claim 1, characterized in that: Ag + The molar amount of loading is 0.025mmol / cm 2 .
3. The NANO-AgI electrode having a regular hexagonal nanostructure according to claim 1, characterized in that: The reaction time after adding the silver ion-containing salt solution to the mixed solution of the polymer dispersant and the iodide ion-containing salt is greater than or equal to 30 minutes.
4. The NANO-AgI electrode having a regular hexagonal nanostructure according to claim 1, characterized in that: In the mixed solution of polyvinyl pyrrolidone and KI, the molar ratio of polyvinyl pyrrolidone to KI is (0.0005~0.004):(0.2~0.7).
5. The NANO-AgI electrode having a regular hexagonal nanostructure according to claim 4, characterized in that: In the mixed solution of polyvinyl pyrrolidone and KI, I + The molar concentration of AgNO3 solution is 1 / 70mol / L~7 / 80mol / L; + The molar concentration is 0.15mol / L~0.6mol / L.
6. The NANO-AgI electrode having a regular hexagonal nanostructure according to claim 1, characterized in that: The NANO-AgI solution is formed into a film on carbon paper by means of infrared lamp baking.
7. The NANO-AgI electrode having a regular hexagonal nanostructure according to claim 1, characterized in that: The stirring speed after adding the silver ion-containing salt solution to the mixed solution of the polymer dispersant and the iodide ion-containing salt is 700 rpm to 900 rpm.
8. A method for preparing a NANO-AgI electrode having a regular hexagonal nanostructure according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Preparation of dispersant and solvent: Heat the polyvinyl pyrrolidone and KI ethylene glycol solution to 60°C to 70°C while stirring at 1000-1500 rpm; Step 2: Introduction of silver source: Add the ethylene glycol solution of AgNO3 to the ethylene glycol solution of polyvinyl pyrrolidone and KI and stir evenly; Step 3: Formation of regular hexagonal nanostructured NANO-AgI solution: The mixed solution obtained in step 2 is reacted at a stirring speed of 700-900 rpm and a reaction temperature of 60° C.-70° C. until the solution becomes a milky white colloid to obtain a NANO-AgI solution; Step 4: Preparation and coating of electrodes: After adding a binder to the NANO-AgI solution obtained in step 3, the solution is coated on carbon paper to form a NANO-AgI electrode with a regular hexagonal nanostructure.
9. Use of the NANO-AgI electrode having a regular hexagonal nanostructure as claimed in any one of claims 1 to 7 in electrocatalytic reduction of carbon dioxide to generate carbon monoxide.
10. The use according to claim 9, characterized in that: The NANO-AgI electrode with regular hexagonal nanostructure is used as the working electrode in the electrocatalytic reaction; the reaction voltage of the working electrode is -1.6V~-1.9V.
Citation Information
Patent Citations
Silver iodide photocatalyst, preparation method and application thereof
CN102989488A
Synthetic method and application of monodisperse silver iodide photocatalyst
CN103586053A